Regularity of the mild solution of a parabolic equation with stochastic measure - Bodnarchuk, I. M.; Боднарчук, І. М. (Institute of Mathematics, NAS of Ukraine, 2017)
We study a stochastic parabolic differential equation driven by a general stochastic measure. The existence, uniqueness, and Holder regularity of the mild solution are established.